MicroRNA Roles in the Nuclear Factor Kappa B Signaling Pathway in Cancer - Wu, Jin’en; Ding, Juntao; Yang, Jing; Guo, Xiaola; Zheng, Yadong (Frontiers in Immunology, 2018)
Nuclear factor kappa B (NF-κB) is a pluripotent and crucial dimer transcription factor that orchestrates various physiological and pathological processes, especially cell proliferation, inflammation, cancer development and progression. NF-κB is transient and tightly regulated in normal cells, but it is activated in cancer cells. Recently, numerous studies have demonstrated miRNAs play a vital role in the NF-κB signaling pathway and NF-κB-associated immune responses, radio- and drug-resistance of cancer, some acting as inhibitors and other as activators. Although it is still in infancy, targeting NF-κB or the NF-κB signing pathway by miRNAs is becoming a promising strategy of cancer treatment.